Clinical outcome measures for monitoring physical function in pediatric obesity: An integrative review. Issue 5 (7th April 2016) - Mahaffey, Ryan; Morrison, Stewart C.; Stephensen, David; Drechsler, Wendy I.
Abstract : Objective: Measuring physical function in children with obesity is important to provide targets for clinical intervention to reduce impairments and increase participation in activities. The objective of this integrative review was to evaluate measurement properties of performance‐based measures of physical function in children with overweight and obesity. Design and Methods: An integrative review of literature published in Cochrane Reviews, SPORTDiscus, CINAHL, PLoS, Medline, and Scopus was conducted. Results: Twenty‐eight studies were eligible and represented 66 performance‐based measures of physical function. Assessments of repeatability and feasibility were not conducted in the majority of performance measures reported; only 6‐min‐timed walk (6MTW) was examined for test‐retest repeatability. Measures of flexibility, strength, aerobic performance, anaerobic performance, coordination, and balance demonstrated construct validity and responsiveness; however, findings were inconsistent across all performance‐based measures. Multi‐item tests of physical function demonstrated acceptable construct validity and responsiveness; however, internal consistency was not determined. Conclusions: There is moderate evidence that 6MTW is suitable for the measurement of physical function in children with obesity. However, evidence is low for the use of aerobic and anaerobic performance, muscle strength, Movement Assessment Battery for Children, and Bruininks‐Oseretsky Test of Motor Proficiency multi‐item performance instruments and very low for flexibility, coordination, and balance tests. Based on this review, measurement of physical function using 6MTW is recommended.